North Sumatra’s business cycle: Sustaining long-term growth and maintaining sectoral credit cycle dynamics - Anna Sumaryati; Dian Prawitasari; Shujahat Ali (Journal of Innovation in Business and Economics, 2025)
This study analyzes sectoral business and credit cycles in North Sumatra using quarterly data from 2012 to 2023. Techniques such as the Hodrick-Prescott Filter, Impulse Response Function, Variance Decomposition in a Vector Auto-Regressive framework, and ARDL are applied. The findings indicate that credit growth in agriculture, trade, and household sectors positively influences the business cycle, while manufacturing credit has a negative impact. The trade sector plays the most significant role in shaping the business cycle. Long-term analysis shows a strong link between economic growth and credit distribution in agriculture, manufacturing, and trade. However, the credit gap in productive sectors decreases while rising in households, highlighting the need for policies to manage short-term credit cycles and foster sustainable growth. The trends suggest opportunities to enhance credit distribution in productive sectors while ensuring financial stability.